Utilisation of outpatient care immediately before emergency admission for ambulatory care-sensitive conditions in Japan: a retrospective observational study - Hirotaka Kato; Rei Goto; Ryotaro Nagashima; Tatsuya Matsuzaki; Takayoshi Nagahama (BMJ Open)
Objective This study assessed whether patients with potentially preventable emergency admissions had limited access to outpatient care immediately before admission and whether they received appropriate outpatient care during their outpatient visits.Design Retrospective observational study.Setting Linked outpatient and inpatient care records obtained from a nationwide claims database in Japan.Participants Patients who experienced emergency admissions for ambulatory care-sensitive conditions between April 2005 and March 2020. Patient and regional characteristics were examined to assess the types of patients who faced difficulties with outpatient visits and receiving outpatient care related to the disease that resulted in admissions (hereafter referred to as admission-related outpatient care).Main outcome measures (1) Whether patients had an outpatient visit during the 2 weeks preceding admission and (2) whether patients received admission-related outpatient care during the 2 weeks before admission.Results This study included 18 449 emergency admissions for ambulatory care-sensitive conditions, representing 16.3% (18 449/113 669) of all emergency admissions in our data. Among patients with emergency admissions for ambulatory care-sensitive conditions, 37.4% did not have an outpatient visit within the 2 weeks preceding admission and 29.9% did not receive admission-related outpatient care despite having an outpatient visit. In total, 67.4% did not receive admission-related outpatient care during the 2 weeks preceding admission. Patients in their 40s and 50s were less likely to have outpatient visits and receive admission-related outpatient care before admission. No evidence associates regional characteristics with outpatient visits and receiving admission-related outpatient care before admission.Conclusion Most patients who underwent emergency admissions for ambulatory care-sensitive conditions did not have an outpatient visit or receive admission-related outpatient care, despite having an outpatient visit immediately before admission. Our findings suggest that emergency admissions may be prevented by improving access to timely and effective outpatient care.